Fortalecimiento de los procesos de crédito en la Cooperativa de Ahorro y Crédito “Ambato” Ltda. - Chango Uñog, José Santos (2023)
The popular and solidarity financial sector at the end of 2022 registered a 28% participation in the financial market, its total assets reached USD 24,955 million, and the main asset account was the credit portfolio that represented 68%, to maintain this participation quota entities must generate value proposals in the granting of credits such as innovation and process automation, a study topic where the problem consists of how to reduce unproductive activities and improve the process of granting microcredits in Cooperativa ¨Ambato¨ Ltda.?. Faced with this question, the objective is to strengthen the processes of granting microcredits to minimize unproductive activities. The design part of the research methodology is Non-experimental, cross-sectional and descriptive, the research was of a mixed type with quantitative and qualitative data analysis.